Evaluating Spider Web Pavement versus Conventional Pavement for Sustainable Road Infrastructure - Irwin; Alpian Nur; Tukimun (International Journal of Industrial Engineering, Technology & Operations Management, 2025)
Road pavement plays a critical role in ensuring the functionality and sustainability of transportation infrastructure, particularly under increasing traffic loads and challenging subgrade conditions. Conventional pavement systems, although widely used, often exhibit performance limitations, such as deformation and differential settlement, when applied to weak soils. This study aims to compare the Spider Web Pavement (slab-on-pile system) with conventional pavement systems in terms of structural performance, technical characteristics, and economic efficiency. A descriptive–comparative methodology based on a systematic literature review was employed to analyze key parameters, including load distribution, pavement thickness, construction complexity, maintenance requirements, and service life. The results indicate that the Spider Web Pavement system provides superior structural performance by efficiently transferring loads to deeper soil layers, significantly reducing subgrade stress and minimizing settlement. It also demonstrates greater resistance to deformation and a longer service life than conventional pavements. However, these advantages are associated with greater construction complexity and higher initial costs. In contrast, conventional pavements offer simpler construction processes and lower upfront investment but require higher maintenance and exhibit shorter service life, particularly under weak subgrade conditions. The findings suggest that while conventional pavements remain suitable for stable soils and cost-sensitive projects, Spider Web Pavement systems offer a more sustainable and cost-effective solution in the long term, especially in geotechnically challenging environments. The study highlights the importance of adopting a life-cycle and performance-based approach in selecting appropriate pavement systems for sustainable road infrastructure development.